Mathematics Course Design Based On Six Questions Cognitive Theory Using Hawgent Dynamic Mathematic Software - Liu CunHua; Zhou Ying; Ouyang Qunzhuang; Tommy Tanu Wijaya (Departement of Mathematics Education, 2019)
In the context of